The Effect of Inquiry-Based Audiovisual Media on The Communication Skills of Biology Students - Yasmawan Yasmawan (Journal of Biological Science and Education, 2020)
Communication skills is ability to explain concepts or materials. This study aimed to determine the effect of inquiry-based audiovisual media on students' communication skills on human excretion material. This quasi-experimental research employed a Post-test – Only Control Grup Design. This study's sample was class XI IPA2 as a learning class taught using audiovisual learning media and class XI IPA1 as a comparison class taught without using audiovisual learning media. Data on students' communication skills was collected by a test and analyzed using a descriptive statistical and inferential analysis using the ttest. The research result indicated that the use of inquiry-based audiovisual media has significantly influenced the students' communication skills on human excretion materialKeywords: Audiovisual Media, Inquiry, Communication Skills